Collaboration as a Village Self-Reliance Ecosystem: Kolaborasi sebagai Ekosistem Kemandirian Desa - Insan, Muhammad Khoirul; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2024)
This study aims to analyze the process of collaboration between the village government, community, and interest groups in achieving village self-reliance programs in Ketapang Village, Indonesia. Using descriptive analysis qualitative research, the study employed purposive sampling to select the village head and village secretary as informants. Data collection techniques included observation and interviews, and data analysis followed Miles and Hubermen's theory of data collection, reduction, presentation, and conclusion. The study used Collaborative Governance theory from Ansell and Gash to measure the questions in the indicators. The results showed that the collaboration between actors was successful, resulting in the construction of the Kalifor tourism village icon as a UMKM development area. The program had a positive impact on economic and social resilience in Ketapang Village. The study highlights the importance of collaborative governance in achieving village self-reliance programs and provides insights for policymakers and practitioners in Indonesia and beyond Highlight : Collaborative Governance: The study used Collaborative Governance theory from Ansell and Gash to measure the success of the collaboration between actors in Ketapang Village. Village Self-Reliance: The study aimed to analyze the process of collaboration between the village government, community, and interest groups in achieving village self-reliance programs in Ketapang Village. Economic and Social Resilience: The program had a positive impact on economic and social resilience in Ketapang Village, highlighting the importance of collaborative governance in achieving village self-reliance programs. Keywords: Collaborative Governance, Village Self-Reliance, Ketapang Village, Indonesia, Economic and Social Resilience